Relative contribution of contact and aerial components in the control of aerial rotation to guide acrobatics skills learning - Haering, D.; Huchez, A.; Blache, Y.; Begon, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The contribution of release state, change in inertia moment, and angular momentum transfer to the performance of a transition move on asymmetrical bars was analysed to better guide acrobatics learning in novices and experts. Numerical simulation based on actual release state was used to optimise aerial technique in novices and experts. Optimised novice performances did not reach actual expert ones. Thereafter, it may be crucial to orient novice learning toward improving release state. In addition for both groups, adjustments of inertia moment and momentum transfer in optimised techniques significantly increased performances. Finally in all actual or optimised techniques, the level of contribution of inertia moment correlated the most with the level of performance. Therefore technique enabling larger change in inertia moment should be preferred.